2022
DOI: 10.1177/10497323221084358
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists Both Reproduce and Resist Biomedical Dominance when Working With People With Low Back Pain: A Qualitative Study Towards New Praxis

Abstract: Despite recommendations to incorporate physical and psychosocial factors when providing care for people with back pain, research suggests that physiotherapists continue to focus on biological aspects. This study investigated how interpersonal and institutional norms influence this continued enactment of the biological aspects of management. We used theoretically-driven analysis, drawing from Foucauldian notions of power, to analyse 28 ethnographic observations of consultations and seven group discussions with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…Although a deeper discussion on therapeutic touch is beyond the scope of this study, our previous work has also observed how this element allowed patients and physical therapists to discuss and attend to nonphysical aspects of LBP. 13 Our finding adds to our previous work and that of Miciak by illustrating how this story-sharing happens in practice and its contribution to balancing power. Hiller et al 14 observed that casual, non-medical conversation during sessions was a key component for relationship building, encouraging active patient participation, and developing trust, supporting our finding that reciprocating the exchange of personal stories is useful for shifting status between parties.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Although a deeper discussion on therapeutic touch is beyond the scope of this study, our previous work has also observed how this element allowed patients and physical therapists to discuss and attend to nonphysical aspects of LBP. 13 Our finding adds to our previous work and that of Miciak by illustrating how this story-sharing happens in practice and its contribution to balancing power. Hiller et al 14 observed that casual, non-medical conversation during sessions was a key component for relationship building, encouraging active patient participation, and developing trust, supporting our finding that reciprocating the exchange of personal stories is useful for shifting status between parties.…”
Section: Discussionsupporting
confidence: 67%
“…This approach allowed a shift from biomedical foci toward more “human” interactions, a shift that has been discussed as difficult for physical therapists working with people with LBP. 13 Finding a similar effect, an interview study by Miciak et al 40 indicated that individuals are interested in knowing their physical therapists stories and that it helps with building therapeutic relationships. Further, personal stories seemed to be shared when therapeutic touch was used.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, the term ‘sociopsychobiomedical’ has been advocated (Department of Health, 2019) to decrease the overwhelming focus on biomedical aspects. Our past work suggests that physiotherapy research (Mescouto, Olson, Hodges, & Setchell, 2022), physiotherapy practice (Dillon et al.; Mescouto, Olson, Hodges, Costa, et al., 2022) and multidisciplinary practice (Mescouto, Olson, Costa, et al., 2022) continue to focus on biological and narrow ‘psychological’ aspects of LBP, with little consideration of the multiple other relevant dimensions. Although some have counter‐argued that psychosocial matters have been overemphasised (Hancock et al., 2011; Jull, 2017), the underlying assumption within the biopsychosocial model seems to lie within a biomedical paradigm despite being established to counter it (Mescouto, Olson, Hodges, & Setchell, 2022).…”
Section: Introductionmentioning
confidence: 99%